A high resolution, hard x-ray photoemission investigation of La_(2-2x)Sr_(1+2x)Mn_2O_7 (0.30 - Jong, S; Massee, F; Huang, Y; Gorgoi, M; Schaefers, F; Fink, J; Boothroyd, A; Prabhakaran, D; Goedkoop, J; Golden, MS (2009)
Photoemission data taken with hard x-ray radiation on cleaved single crystals of the bilayered, colossal magnetoresistant manganite La_(2-2x)Sr_(1+2x)Mn_2O_7 (LSMO) with 0.30